2002
DOI: 10.1097/00010694-200212000-00001
|View full text |Cite
|
Sign up to set email alerts
|

HEATS OF K/Ca AND K/Pb EXCHANGE IN TWO TROPICAL SOILS AS MEASURED BY FLOW CALORIMETRY 1

Abstract: Flow calorimetry can provide useful information about surface chem ical reactions in soils that cannot be obtained readily by other methods. When flow calorimetry is conducted over a range of surface coverages, different sorption heats can be calculated to yield information about how binding energies vary with coverage, i.e., surface heterogeneity. The purpose of this study was to determine heats of exchange for K/Ca and K/Pb systems using flow calorimetry and to evaluate the degree of sur face heterogeneity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…1b, d) indicate that as K � Gast, 1972). Consistent with the the amount of K � (preferred ion) on the exchanger above, Appel et al (2002) observed no changes in the decreases, its selectivity increases (going from left to enthalpy of either Ca 2� or Pb 2� adsorption with inright on the figures). Contrarily, the Oxisol-Ca and -Pb creased surface coverage of these ions on this soil.…”
Section: Determination Of Calcium and Lead Selectivitysupporting
confidence: 67%
“…1b, d) indicate that as K � Gast, 1972). Consistent with the the amount of K � (preferred ion) on the exchanger above, Appel et al (2002) observed no changes in the decreases, its selectivity increases (going from left to enthalpy of either Ca 2� or Pb 2� adsorption with inright on the figures). Contrarily, the Oxisol-Ca and -Pb creased surface coverage of these ions on this soil.…”
Section: Determination Of Calcium and Lead Selectivitysupporting
confidence: 67%
“…The flow calorimeter used in this experiment was the same one used by Appel et al (2002) and Kabengi et al (2006a, b), and its operation has been described in previous work . The only changes to the instrument were in design of the sample cell, which will be described in a future publication (Adrian Gale; personal communication) and that the column effluent in the current experiment passed through a cell with a G-P Gel Combo glass electrode (Corning, Corning, NY) linked to an Accumet 1002 potentiometer (Fisher Scientific, Fairlawn, NJ), enabling the in-line measurement of the effluent solution pH.…”
Section: Instrumentationmentioning
confidence: 99%
“…Briefl y, this involves the use of a calorimeter for the detection of changes in heat emitted (exotherm) or absorbed (endotherm) as a solute is added to a solution or suspension. Such instruments have been used in the investigation of sorption mechanisms and thermodynamics (Kabengi et al, 2006a;Cai et al, 2006;Kaya, 2004;Rhue et al, 2002;Miltenburg and Golterman, 1998;Zou et al, 1997), ion exchange (Kabengi et al, 2006b;Appel et al, 2002), and surface charge (Kabengi et al, 2006b). Calorimetric techniques are not "stand alone," however; correct interpretation of the data involves some knowledge of the system being studied and complimentary solution or solid-state data.…”
Section: Investigating Phosphorus Sorption Onto Kaolinite Using Isothmentioning
confidence: 99%